Acute results of a novel flexible tip radiofrequency catheter incorporating contact force sensing. (19th May 2022) - Nair, D; Martinek, M; Colley, J; Sundaram, S; Sharma, S; Morales, G; Sommer, P; Healy, S; Siddiqui, U; Williams, C; Sarver, A; Lo, M
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: Catheter ablation is an established therapy for paroxysmal atrial fibrillation (PAF). The TactiFlex Ablation Catheter, Sensor-Enabled (TactiFlex SE) is a next-generation radiofrequency ablation catheter incorporating highly accurate fiber optics-based contact force sensing technology with a flexible, laser-cut tip. This is the first report of results from the TactiFlex IDE clinical study. Purpose: To demonstrate that ablation with TactiFlex SE is safe and effective for the treatment of drug refractory, symptomatic PAF. Methods: The TactiFlex IDE (NCT04356040) is a prospective, non-randomized, multi-center clinical study which enrolled 305 subjects worldwide in the main study. Enrollment in the main study began on June 26, 2020 and completed on June 8, 2021. Subjects underwent de novo Pulmonary Vein Isolation (PVI) and, if indicated, a Cavotricuspid Isthmus ablation (CTI line) for CTI-dependent atrial flutter. Results: Acute procedural success was achieved in 98.6% (274/278) of the main study cohort who underwent an ablation procedure using the TactiFlex SE. First pass success, defined as isolation of all pulmonary veins (PVs) confirmed after a minimum 20 min waiting period was achieved in 89.6% (249/278) of subjects. This was a significant improvement versus the TactiSense IDE trial (TactiCath Ablation Catheter, Sensor-Enabled). Significant decreases were also seen in total procedure time (123 min [101.0, 163.5]), total PV ablation time (55.5 min [35.0, 81.0]), total fluoroscopy time (6.0 min [0.0, 13.0]) and irrigation fluid volume (450.0 mL [346.0, 636.0]) (values given as Median [Q1, Q3]), see FIGURE. All subjects have completed at least 90 days of follow-up. Only 2.6% (7/271) of subjects required a repeat procedure during the 90-day blanking period. The primary safety and effectiveness endpoints will be evaluated at 12-months. At 90 days, 4.3% (12/281) subjects had experienced a primary safety endpoint event. Conclusions: The acute data from the TactiFlex IDE clinical study demonstrate safety and effectiveness of the TactiFlex SE catheter in the treatment of PAF. Ablation procedures performed using the next-generation TactiFlex SE catheter were shorter and had improved acute clinical effectiveness outcomes versus the TactiSense IDE. It is anticipated these results will also be reflected in the 12-month safety and effectiveness endpoints.